Economics of Tobacco Toolkit, Tool 2. Data for Economic Analysis - Czart, Christina; Chaloupka, Frank (World Bank, Washington, DC, 2013)
This tool provides a general introduction to 'the art' of building databases. It addresses a number of issues pertaining to the search, identification and preparation of data for meaningful economic analysis. It can best be thought of as a reference mechanism that provides support for the occasionally frustrated but endlessly hungry researcher working through the adventures of tobacco control analysis. Anyone can reference this tool. This tool addresses a variety of data issues as they pertain to the economic analyses presented in the remaining tools of this toolkit. Most countries in the world today report at least a basic set of national economic and social information. In addition, aggregate or 'macro' level data is also largely available at sub-national levels of these societies and captures information that's reflective of regional, state, provincial, county or other jurisdictional divisions of the country. Consumption represents product use. Therefore, data on tobacco consumption reflects the amount of tobacco products used by a consumer. Data on tobacco product consumption is required for any economic analysis related to the demand for tobacco. Tobacco consumption information can be obtained through surveys of households and/or individual consumers. National population surveys and censuses interview random samples of individuals and/or households in an effort to obtain behavioral and socioeconomic information that will best describe the characteristics of the nation's current population.